Development of Video Learning Materials on Computational Thinking in Class XI Students of Private High School Tunas Kelapa Samarinda Academic Year 2024/2025 - Nadilla Putri Mulyadi; Galih Yudha Saputra (Politeknik Pertanian Negeri Samarinda, 2025)
In the digital era, science and technologies are developing so fast, it’s also influences developments of students’ mindset and character in learning. so the Indonesian governments try to improve the existing curriculum of the name “Kurikulum Merdeka”. In this curriculum, students are required to have high order thinking skill levels to support their lives in keeping up with changing times. Of course, it’s also requiring teachers to be more creative and provide innovation in the teaching and learning process. The aim of the research is to develop learning media products in the form of videos learning and see the eligibility of the product being developed and implement the product for students whose result is the form of pretest and posttest scores and N-Gain scores to determine whether it's works to improve student learning outcomes. The method used in this research is Research and Development (R&D) with the ASSURE model (Analyze, State, Select, Utilize, Require, Evaluate, and Revise). The results of the eligibility test carried out by three media and one material expert were analyzed using a Likert scale. For the respective results obtained of the three media expert were 93%, 92%, 96% with an average of 93% which was included in the very eligible category, and the result from the material experts is 98% with “very eligible” category. Then for the results of the product implementation in the form of a pretest score with an average of 38, a posttest score with an average of 96, an average N-Gain Score of 0,95 and a percent of N-Gain is 95% which was included in the “high” dan “effective” category. Based on the results of this assessment, it can be concluded that the development of video learning materials on computational thinking in 11th grade class at Private High School Tunas Kelapa Samarinda is “very eligible” to be used in the learning process and is effective in improving student learning outcomes.